Laser Engineering Net Shaping of Microporous Ti6Al4V Filters - Gualtieri, Thomas; Bandyopadhyay, Amit (Frontiers in Mechanical Engineering, 2016)
In many applications porous metal structures are necessary for proper and optimal function. Yet these structures can be difficult to build. It is especially difficult if the pore size desired is very fine or on the micro scale. For this reason, additive manufacturing processes have been looked at to build these structures. In this study LENS processing was experimented with to see if it could be a viable process to create micro-porous interconnected structures. Using Ti6Al4V and only changing processing parameters, porous structures were created having porosity ranging from 21.5% to 15.4%. The microstructure proved to be that of traditional laser processed Ti6Al4V parts. Compression test of the samples showed that the ultimate compressive strength varied from 645-556MPa. Overall LENS proved to be a viable method to make unique micro-porous interconnected structures that could be easily added to any build without having to change the design.